Application of the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) in the Assessment of Educational Personnel Performance - Sefrika Sefrika; Dini Setyorini; Helina Apriyani (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2026)
Educational staff performance assessment is an important aspect in human resource management in educational environments because it influences service quality and organizational effectiveness. However, the performance assessment process often faces problems in the form of assessor subjectivity and the large number of criteria that must be considered, so a system that can assist objective decision-making is needed. This study aims to apply the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to the Decision Support System for educational staff performance assessment. The research method used is a quantitative approach by utilizing data from observations, interviews, and documentation. The criteria used in the study include competence, work discipline, attendance, responsibility, work quality, and cooperation. The calculation process is carried out through the stages of compiling a decision matrix, normalization, weighting, determining positive and negative ideal solutions, and calculating preference values to produce alternative rankings. The results show that alternative A3 obtained the highest preference value of 0.682 so it is recommended as the educational staff with the best performance, followed by alternative A7 with a value of 0.633 and alternative A10 with a value of 0.578. The research results demonstrate that the TOPSIS method is capable of producing a more objective, transparent, and measurable assessment process, thus assisting leaders in effectively identifying the best educational staff. Furthermore, the application of the TOPSIS method to a Decision Support System can improve the quality of decision-making in evaluating educational staff performance.